The Effect of Realistic Mathematics Education (RME) Learning Approach on the Ability to Recognize Number Concepts in Children Aged 4-5 Years - Indah Puspita Sari; Jhoni Warmansyah; Restu Yuningsih; Meliana Sari; Rahayu Yandira (Journal of Islamic Education Students, 2023)
This research aims to determine the effect of a realistic mathematics learning approach (PMR) on the ability to recognize the concept of numbers. This research is a quantitative research with pre-experimental design. This research was conducted at Pertiwi Batusangkar Kindergarten, Tanah Datar District. The data collection technique in this study is total sampling. In general, the results of this study indicate that the open-ended learning approach has a significant effect, that t0 is greater than the tt value table (14.01> 2.9980), so the null hypothesis (h0) proposed is rejected and the alternative hypothesis (ha) accepted to develop the ability to recognize children's number concepts at the age of 4-5 years. Thus the realistic mathematics education learning approach (PMR) has an effect on the introduction of the concept of numbers in early childhood.